Kemampuan Berbahasa Hubungannya dengan Perkembangan dan Fungsi Otak - Akhyar, Fitria (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The function of the right hemisphere is for alertness, recognition of conditions, eye contact, socialization, emotional control, intuition, turn-taking, nonverbal, pragmatic, visiospasial, holistic thinking, art, and creativity. While the left hemisphere function is to speak, read, write, count, and linear-analytical thinking. The process of lateralization or specialization of the hemispheres greatly influences the development of speech (language acquisition). In the process of development, all normal children or experiencing a reasonable growth acquire a language, the first language or the mother tongue in the first years of life. Furthermore, the development of speech and language is an important indicator of childrens progress and are very sensitive to disturbances in the development of other areas, ie, areas of cognitive, sensory-motor, psychological, and emotional. Child language acquisition consists of several stages, i.e.: (1) babbling; (2) one-word stages (holofrastis); (3) two-word phases; and (4) telegraphic speech.